Identificación genotípica de Staphylococcus con fenotipo meticilino resistente aislados de muestras de humanos, animales y ambiente - Espejo, Luis José (2019)
The aim of this study was to identify the mecA-1 gene of Staphylococcus isolates with methicillin-resistant phenotype (SMR) obtained from biological samples and surfaces of a veterinary clinic. Nine isolates with SMR phenotype classified by the automated VITEK system were selected. The genus and the variability were corroborated by amplification and sequencing of the 16S rRNA and tuf genes. The presence of the mecA- 1 gene was also established by PCR. In the nine isolates with SMR phenotype, the 16S rRNA and tuf genes were identified, showing 99% similarity with reference strains; however, only in five isolates was found the mecA-1 gene. The results showed a greater identification of the MR genotype in intra-hospital surfaces, which indicates the need for control and monitoring of these strains in veterinary hospitals due to the implications they have on public health.